2020
DOI: 10.1111/jse.12659
|View full text |Cite
|
Sign up to set email alerts
|

Endo‐allopolyploidy of autopolyploids and recurrent hybridization—A possible mechanism to explain the unresolved Y‐genome donor in polyploidElymusspecies (Triticeae: Poaceae)

Abstract: The genus Elymus L. in the tribe Triticeae (Poaceae) includes economically and ecologically important forage grasses. The genus contains the pivotal St genome from Pseudoroegneria in combination with other genomes in the tribe. Many Elymus species are tetraploids containing the StY genomes. It is thought that polyploidization characterizes the speciation of the genus in which the Y is considered as another key genome. Based on data from cytological, genome in situ hybridization, and molecular studies, we hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…The concept of nucleocytoplasmic interaction (NCI) hypothesizes that specific chromosome rearrangement plays an important role in restoring fertility and nucleocytoplasmic compatibility for the genetic stabilization of newly formed hybrids and polyploids ( Gill, 1991 ; Jiang and Gill 1994 ). In E. nutans , heteroplasmy and variation in mitochondrial genes have been identified among individuals ( Liu et al., 2020 ). Whether the fertility of the heterozygote is affected by NCI still requires further investigation in E. nutans.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of nucleocytoplasmic interaction (NCI) hypothesizes that specific chromosome rearrangement plays an important role in restoring fertility and nucleocytoplasmic compatibility for the genetic stabilization of newly formed hybrids and polyploids ( Gill, 1991 ; Jiang and Gill 1994 ). In E. nutans , heteroplasmy and variation in mitochondrial genes have been identified among individuals ( Liu et al., 2020 ). Whether the fertility of the heterozygote is affected by NCI still requires further investigation in E. nutans.…”
Section: Discussionmentioning
confidence: 99%
“…E. nutans is an allopolyploid with a genome constitution of StStHHYY (2 n = 6 x = 42). The St genome originates from the genus Pseudoroegneria , the H genome from Hordeum , and the Y genome’s origin is unknown and still on debating ( Wang et al, 1994 ; Lei et al, 2022 ; Liu et al, 2022 ). E. nutans distributed on the Qinghai-Tibet Plateau show highly divergent adaptation, growing on grassland, bushland, wetland, mountain slopes, and swales, at altitudes from 1,000 to 5,000 m, and is tolerant to various environmental stresses associated with high altitudes, such as cold and drought.…”
Section: Introductionmentioning
confidence: 99%
“…Dewey ( 1984 ) considered that the Y genome has its origin in Central Asia or the Himalaya region, and may be extinct. Extensive cytogenetic and molecular studies have suggested that the St ( Pseudoroegneria ), W [ Australopyrum (Tzvelev) Á. Löve], V [ Dasypyrum villosum (L.) Candargy], and Xp [ Peridictyon O. Seberg, S. Frederiksen & C. Baden] genomes are potential donors of the Y genome (Fan et al., 2013 ; Lei et al., 2022 ; Liu et al., 2006 , 2022 ; Sun & Komatsuda, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The tetraploid species Roegneria alashanica Keng was found to have the StSt Y genome constitution (Wang & Jensen, 2017), suggesting that the Y genome might derive from St through StY. Dewey (1984) (Fan et al, 2013;Lei et al, 2022;Liu et al, 2006Liu et al, , 2022Sun & Komatsuda, 2010).…”
mentioning
confidence: 99%